Implementasi Guided Reciprocal Peer Questioning (GRPQ) untuk Meningkatkan Kemampuan Memahami Bacaan Siswa SMK - Fibriani Dita Puspitasari; Ely Faridah; Hanan Latifah; Endang Lusi Supartini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Reading is an essential skill in learning English besides Listening, Speaking, and Writing. But unfortunately, based on the latest PISA test, students’ reading comprehension ability in Indonesia is low. This study aims to investigate how Guided Reciprocal Peer Questioning (GRPQ) improves students' reading comprehension. The researcher uses the GRPQ definition from Gillies et al. (2008) to facilitate student group interactions and implements classroom strategies based on King (1994) Wells' (1987) theory on informational literacy reading also provides a theoretical basis. Conducted as action research, this study involved 36 eleventh-grade students at a Public Vocational High School in Surakarta during the second semester of the 2023/2024 academic year. Data were collected through observation, tests, and questionnaires over two research cycles. Results indicate that the GRPQ strategy significantly enhances reading comprehension, shown by improved test scores across cycles. Observations also noted better teacher performance and positive student feedback. Initially, students faced challenges like limited vocabulary, lack of topic knowledge, and grammar difficulties, but these improved with GRPQ. Adjustments in the second cycle, such as clearer instructions, further improved the strategy's effectiveness. The study suggests GRPQ can boost reading skills, confidence, motivation, and create a supportive learning environment, recommending its use in education.